Sapo tem mão? - Souza, Aracelly Oliveira Franco; Barros, Cleber Miranda; Nunes, Geisa Oliveira; Araújo, Inês Cassia Lima Silva; Alves, Joana Darc Xavier; Correa, João Batista Lopes; Maia, Vanilda Fátima; Souza, Vanderleia Costa; Oliveira, Wania Rosa Siqueira (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf